How Digital Capabilities Drive SME Performance: The Mediating Role of Business Innovation and the Moderating Role of Resilience - Zuriyati Paziah; Muh. Fahrurrozi; Qurratul Aini (LP2M IAIN Palopo, 2026)
Objective This study examines the influence of digital literacy, digital technology utilization, and entrepreneurial orientation on MSME performance, with business innovation as a mediating variable and business resilience as a moderating variable in the digital era. Design/Methodology/Approach A quantitative survey approach was applied to 220 MSME operators in East Lombok Regency, analyzed using PLS-SEM to test direct, indirect, and moderating effects. Findings Digital technology adoption, business innovation, business resilience, and digital literacy positively and significantly affect MSME performance. Entrepreneurial orientation indirectly influences performance through business innovation. Digital literacy does not significantly affect business innovation. Business innovation mediates the relationship between digital technology adoption, entrepreneurial orientation, and MSME performance. Business resilience moderates only the innovation–performance relationship. The model shows strong explanatory power (R² = 0.736; Q² = 0.650). Practical Implications MSME owners should optimize digital technology use and continuously innovate. Government and stakeholders should promote digital literacy and business resilience programs to sustain MSME growth. Originality/Value This study integrates digital literacy, digital technology adoption, entrepreneurial orientation, business innovation, and business resilience into a comprehensive model, uniquely positioning innovation as a mediator and resilience as a moderator of MSME performance.